Antiviral B cell and T cell immunity in the lungs - Chiu, Christopher (Nat Immunol, 2014)
Respiratory viruses are frequent causes of repeated common colds, bronchitis and pneumonia, which often occur unpredictably as epidemics and pandemics. Despite those decimating effects on health and decades of intensive research, treatments remain largely supportive. The only commonly available vaccines are against influenza virus, and even these need improvement. The lung shares some features with other mucosal sites, but preservation of its especially delicate anatomical structures necessitates a fine balance of pro- and anti-inflammatory responses; well-timed, appropriately placed and tightly regulated T cell and B cell responses are essential for protection from infection and limitation of symptoms, whereas poorly regulated inflammation contributes to tissue damage and disease. Recent advances in understanding adaptive immunity should facilitate vaccine development and reduce the global effect of respiratory viruses.